Galvanostatic Growth of Passivating Films Under Transient Conditions. I. Model and Quantitative Analysis for the Zn/ZnO System - DAlkaine,C.V. (2003)
On the basis of an ohmic model and a Tafel equation describing relations between current density and overpotentials in the film and at the metal/film interface, respectively, it is shown that a quantitative analysis of galvanostatic transients for the growth of passivating ultra-thin films on the so-called non-noble metals can be obtained. As an example, the growth of ZnO on Zn in a boric/borate buffer solution is considered. In this case, the values of the transfer coefficient and the exchange current density of the reaction at the metal/film interface were found to be 1.2 and 0.11 mA cm-2, respectively. It was shown that a single, first film occurred at low current densities and two films at high ones. The ionic resistivity inside the single, first film, during the transients, has an initial constant value region followed by a final increase indicating the aging process. For this variation the evolution of the point defect concentrations is taken into account. For the variation of the ionic resistivity with the galvanostatic current density two types of behaviors were found, depending on the current density. An interpretation of these results is advanced in terms of the concentrations, mobilities and recombination rate of point defects inside the film.